2018
DOI: 10.3390/inorganics6010022
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Pyridyl-NHC-Ligated Rhenium Photocatalyst for CO2 Reduction in the Presence of Water and Oxygen

Abstract: Re(pyNHC-PhCF 3 )(CO) 3 Br is a highly active photocatalyst for CO 2 reduction. The PhCF 3 derivative was previously empirically shown to be a robust catalyst. Here, the role of the PhCF 3 group is probed computationally and the robust nature of this catalyst is analyzed with regard to the presence of water and oxygen introduced in controlled amounts during the photocatalytic reduction of CO 2 to CO with visible light. This complex was found to work well from 0-1% water concentration reproducibly; however, tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…A number of earth-abundant metal complexes have been reported that are capable of catalyzing CO 2 reduction to CO or HCO 2 – through visible light-driven reactions. Very recently, molecular transition metal catalysts capable of producing methane from carbon dioxide and visible light have emerged; however, reports of this reaction are rare. , Even more rare is the light-driven catalytic reduction of carbon dioxide to methane in the presence of solvent quantities of water . In fact, the vast majority of molecular photocatalytic systems for CO 2 reduction utilize anhydrous solvents such as acetonitrile or N , N -dimethylformamide . In general, improvements to the durability of photocatalytic CO 2 reduction systems are greatly needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of earth-abundant metal complexes have been reported that are capable of catalyzing CO 2 reduction to CO or HCO 2 – through visible light-driven reactions. Very recently, molecular transition metal catalysts capable of producing methane from carbon dioxide and visible light have emerged; however, reports of this reaction are rare. , Even more rare is the light-driven catalytic reduction of carbon dioxide to methane in the presence of solvent quantities of water . In fact, the vast majority of molecular photocatalytic systems for CO 2 reduction utilize anhydrous solvents such as acetonitrile or N , N -dimethylformamide . In general, improvements to the durability of photocatalytic CO 2 reduction systems are greatly needed.…”
Section: Introductionmentioning
confidence: 99%
“…Tetraaza (N 4 ) macrocycles supporting earth-abundant transition metals have produced some of the highest turnover numbers in CO 2 reduction catalysis . Additionally, electron-rich N -heterocyclic carbenes (NHCs) have engendered more robust CO 2 reduction catalysts in recent examples because they provide strong metal–ligand bonding interactions. ,, Combining these two stabilizing features into a single complex is highly desirable, and Jurss and coworkers have recently shown the electrocatalytic reduction of CO 2 to CO with two NHC-ligated macrocyclic nickel complexes …”
Section: Introductionmentioning
confidence: 99%
“…Later, the same authors probed the role of the criticalto-reactivity 4-CF 3 group computationally. [63] The NHC-based ligand on 31 a was shown to have single occupied molecular orbital (SOMO) delocalization onto the 4-CF 3 ring after the catalyst was reduced with a planarization of the ligand πsystem. Through time-correlated single photon counting studies, complex 31 a was found to have a significant shorter excited-state lifetime than [Re(bpy)(CO) 3 Br].…”
Section: Photoreduction Of Comentioning
confidence: 99%
“…Through time-correlated single photon counting studies, complex 31 a was found to have a significant shorter excited-state lifetime than [Re(bpy)(CO) 3 Br]. [63] Further studies were performed to explore two different aspects: (i) the impact of several electron withdrawing substituents (CF 3 , bis CF 3 , NO 2 , CN) on the aryl group of the py-NHC-aryl ligand (complexes 31 a-31 d, Scheme 25) and (ii) the impact of extending conjugation along the backbone of the ligand (complex 35, Scheme 25). [64] Notably, all complexes acted as direct photocatalysts for the CO 2 reduction reaction in the presence of a sacrificial SD with different TON and TOF values (entries 5-8, Table 3).…”
Section: Photoreduction Of Comentioning
confidence: 99%
See 1 more Smart Citation